Missing Part of Halal Supply Chain Management - Hendayani, Ratih; Fernando, Yudi (IGI Global USA, 2018)
The awareness about halal products in the world, especially about halal foods, is increasing. Not only 1.57 billion Muslims in the world spreading over 57 Islamic countries (Halal Trade Globally, 2015), but many non-Muslims also regard halal products, halal foods especially, as a trend of a healthy lifestyle. This is an opportunity for certified halal foods manufacturers to make their halal products as a competitive advantage, of which the other food companies do not possess. Regarding the production processes, the label “halal foods” must not be a mere proclamation made by the manufacturers. Halal food producers must start managing their supply chain, particularly to decide and inspect on where they obtain the raw halal material and to ensure the optimal cleanliness and hygiene in the distribution, to ascertain that the raw materials or processed foods are free of contamination which may cause the products to become not halal. In fact, according to Zulfakar et al. (2014), with the complexity of the food trade in the world, especially in terms of distributing halal products throughout the world, consumers of halal food products are still not sure whether the products produced are completely in accordance with the principles of halal or the Sharia laws, whether or not the food is contaminated when distributed to the whole world.